Elucidating the major hidden genomic components of the A, C, and AC genomes and their influence on Brassica evolution. Issue 1 (December 2017) - Perumal, Sampath; Waminal, Nomar; Lee, Jonghoon; Lee, Junki; Choi, Beom-Soon; Kim, Hyun; Grandbastien, Marie-Angèle; Yang, Tae-Jin
Abstract Decoding complete genome sequences is prerequisite for comprehensive genomics studies. However, the currently available reference genome sequences ofBrassica rapa (A genome), B .oleracea (C) andB .napus (AC) cover 391, 540, and 850 Mbp and represent 80.6, 85.7, and 75.2% of the estimated genome size, respectively, while remained are hidden or unassembled due to highly repetitive nature of these genome components. Here, we performed the first comprehensive genome-wide analysis using low-coverage whole-genome sequences to explore the hidden genome components based on characterization of major repeat families in theB .rapa andB .oleracea genomes. Our analysis revealed 10 major repeats (MRs) including a new family comprising about 18.8, 10.8, and 11.5% of the A, C and AC genomes, respectively. Nevertheless, these 10 MRs represented less than 0.7% of each assembled reference genome. Genomic survey and molecular cytogenetic analyses validates ourinsilico analysis and also pointed to diversity, differential distribution, and evolutionary dynamics in the threeBrassica species. Overall, our work elucidates hidden portions of threeBrassica genomes, thus providing a resource for understanding the complete genome structures. Furthermore, we observed that asymmetrical accumulation of the major repeats might be a cause of diversification between the A and C genomes.